Comparison Study of Leading Rotary Steerable System and Future Development Trend. Issue 1 (April 2021) - Fei, Li; Xue-ying, Ma; Yu-qi, Tan
Abstract: The rotary steerable system is critical drilling equipment urgently needed in the development of unconventional oil and gas fields in China. It is still a significant but unavailable technology for China's petroleum industry. With the high demand for rotary steerable system in unconventional oil and gas development, this paper studies RSS tools from major oilfield service companies. Different tools from major oilfield service companies and their technical specifications were studied. Firstly, the development history of the rotary steerable system is introduced, and the tools are then classified into different categories based on control and biasing methodologies. The key technical parameters of the RSS were compared and analyzed. Moreover, a detailed comparison of the 475, 675 and 900 series of tools has been carried out. The current development focuses of rotary steerable tools include high dogleg severity, high temperature and high pressure and integrated navigation scheme with inertial and magnetic methods. Finally, the development trends of the RSS were forecasted. The objective of this paper is to provide an overview and latest development of the rotary steerable system for developer, operation and maintenance population in the drilling industry.